Ekonomi Biru, Pertumbuhan Biru, dan Keadilan Sosial: Perspektif Akuntansi - Falah, Muhammad Helmi; Aptasari, Fety Widianti (Jurnal Ilmiah Wahana Akuntansi, 2025)
This study aims to explore the need for accounting system reform in the context of coastal and marine development based on the principles of the Blue Economy to promote socio-ecological justice. Using a literature review method, the research analyzes various alternative accounting approaches capable of capturing the social, cultural, and ecological dimensions of marine development. The core emphasis lies in the importance of integrating full-cost accounting, natural capital accounting, and social return on investment (SROI), as well as the active involvement of local communities in the documentation and evaluation processes of coastal projects. The findings reveal that conventional accounting approaches fail to represent the inequities in the distribution of development benefits and burdens, highlighting the need for more inclusive and participatory methods to address these gaps. This study recommends the adoption of a more holistic and justice-based accounting system as a tool for fair, transparent, and sustainable reporting in coastal and marine development projects.